Treatment of adult acquired umbilical hernias - Mañana, Julio (Cirugía del Uruguay, 2020)
A therapeutic procedure for treating umbilical hernia not showing important unusual elements in considered, and an eclectic summary of the diffeterent techniques hither to published is presented.